Congenital Ewing's Sarcoma/Peripheral Primitive Neuroectodermal Tumor: A Case Report and Review of the Literature - Shu-Guang Jin; Xiao-Ping Jiang; Lin Zhong (Pediatrics and Neonatology)
Ewing's sarcoma (EWS) and peripheral primitive neuroectodermal tumor (pPNET) are small round cell malignancies that develop in soft tissue and bone. They very rarely affect newborns. A diagnosis of EWS/pPNET depends mainly on immunohistochemistry and molecular/genetic assays. Since these tumors are highly aggressive, patient prognosis is typically very poor, and treatment remains a challenge. Here, we report a 13-day-old newborn diagnosed with congenital EWS/pPNET and describe its treatment.